The Impact of Employer Branding and Social Media on Employer of Choice on Islamic Bank in Attracting Generation Z in Indonesia - Anwar Mattawappe; Ryan Saputra Alam; ⁠Salahuddin Alam; Abdul Awim (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Islamic banks in Indonesia face challenges in attracting Generation Z talent despite being the largest Muslim-majority country with a growing Islamic banking industry. Generation Z has different characteristics from previous generations, and Islamic banks must compete with conventional banks and other industries for the best talent. This study examines the effect of employer branding dimensions and social media on employer of choice for Islamic banks among Generation Z in Indonesia. Method: This quantitative study surveyed 355 undergraduate Muslim students from both Islamic and general universities in East Java, Indonesia, representing Generation Z (born 1995–2010). Data were collected through online questionnaires distributed via Google Classroom. Structural Equation Modeling (SEM) with LISREL 8.80 was used to analyze the relationships between employer branding dimensions (work culture, ethics & CSR, salary, diversity), social media, person-organization fit, organizational attractiveness, and employer of choice. Results: The findings reveal that only two employer branding dimensions salary and ethics & CSR positively influence person-organization fit and organizational attractiveness. Social media significantly affects person-organization fit and organizational attractiveness but does not directly influence employer of choice. Work culture and diversity show no significant effects. Person-organization fit and organizational attractiveness positively influence employer of choice. Conclusion: Islamic banks should emphasize salary competitiveness and ethics & CSR communication while optimizing social media to build organizational attractiveness. However, social media alone is insufficient to convert attraction into application decisions. Islamic banks need comprehensive strategies beyond social media promotion to successfully attract Generation Z talent.